NSP-Dependent Simple Nitrile Formation Dominates upon Breakdown of Major Aliphatic Glucosinolates in Roots, Seeds, and Seedlings of Arabidopsis thaliana Columbia-0 - Wittstock, Ute; Meier, Kathrin; Dörr, Friederike; Ravindran, Beena M. (Frontiers in Plant Science, 2016)
One of the best-studied plant defense systems, the glucosinolate-myrosinase system of the Brassicales, is composed of thioglucosides known as glucosinolates and their hydrolytic enzymes, the myrosinases. Tissue disruption brings these components together, and bioactive products are formed as a consequence of myrosinase-catalyzed glucosinolate hydrolysis. Among these products, isothiocyanates have attracted most interest as chemical plant defenses against herbivores and pathogens and health-promoting compounds in the human diet. Previous research has identified specifier proteins whose presence results in the formation of alternative product types, e.g. nitriles, at the expense of isothiocyanates. The biological roles of specifier proteins and alternative breakdown products are poorly understood. Here, we assessed glucosinolate breakdown product profiles obtained upon maceration of roots, seedlings and seeds of Arabidopsis thaliana Columbia-0. We identified simple nitriles as the predominant breakdown products of the major endogenous aliphatic glucosinolates in root, seed, and seedling homogenates. In agreement with this finding, genes encoding nitrile-specifier proteins (NSPs) are expressed in roots, seeds, and seedlings. Analysis of glucosinolate breakdown in mutants with T-DNA insertions in any of the five NSP genes demonstrated, that simple nitrile formation upon tissue disruption depended almost entirely on NSP2 in seeds and mainly on NSP1 in seedlings. In roots, about 70-80 % of the nitrile-forming activity was due to NSP1 and NSP3. Thus, glucosinolate breakdown product profiles are organ-specifically regulated in A. thaliana Col 0, and high proportions of simple nitriles are formed in some parts of the plant. This should be considered in future studies on biological roles of the glucosinolate-myrosinase system.